CLINICAL EFFICACY OF VALUKA SWEDA WITH AMLAKANJI IN VATAKANTAKA: A CASE STUDY - S, Vijayalakshmi; A, Muralidhar; T.N, Mahesh; A, Byresh (International Journal of Ayurveda and Pharma Research, 2015)
Vatakantaka is a disease explained by Sushruta in the context of Vatavyadhi as a painful condition of heel caused by its improper placement of foot on the ground. Pain beneath the heel is seen in infra calcaneum bursitis and plantar fasciitis. Plantar fasciitis is a common cause for pain in the heel region, which occurs in about 10% of the general population and represents 10 to15% of foot problems requiring professional care. Women are twice as likely as men to get plantar fasciitis. Vatakantaka is very common condition that affects normal routine work. A case with chronic Vatakantaka managed successfully by Valukasweda with Amlakanji is reported here. A 57 year old female complaining of pain in the right heel and other associated symptoms, with the X-ray of the right ankle joint report showing heel spurs was treated with Sthanikaabhyanga using Pindataila followed by Valukasweda with Amlakanji for eight days showed significant results in the subjective parameters and also marked reduction was noted in the size of the heel spur in X-rays taken before and after treatment. It is the need of hour to focus such practises which yields good results and are not much expensive.